Pengaruh Kompetensi Profesional Dan Keteladanan Guru Terhadap Akhlak Siswa Di MTSN 9 Hulu Sungai Tengah - Cahyadi, Ani; Liana, Lisa (el Buhuth: Borneo Journal of Islamic Studies, 2020)
This study aims to determine the effect of professional competence on students' morals, to determine the influence and exemplary attitude towards student morals and to determine the effect of professional competence and teacher exemplary on student morals at MTsN 9 Hulu Sungai Tengah. The method used in this study is a quantitative method using multiple correlations to determine the closeness of the relationship between the variables of professional competence (X1) and teacher exemplary (X2) on student morals (Y.) The population in this study were all class IX students of MTsN 9 Hulu. Sungai Tengah, which amounts to 158 people with a total sample of 61 people, uses the Slovin formula. The results showed that the effect of professional competence and teacher exemplary on student morals at MTsN 9 Hulu Sungai Tengah in 2020 can be concluded as follows: First, there is a very significant difference between professional competence and student morals. From the calculation of the correlation between X1 to Y amounted to 18.1%. Second, there is a significant influence between the exemplary teacher and student morals. From the results of the calculation of the correlation between X2 and Y of 50.9%. Third, there is a very significant influence between professional competence and teacher exemplary together on student morals. From the results of the calculation of the correlation using multiple regression analysis, it was found that the correlation R between X1 and X2 simultaneously to Y was 51.1%.